An online decision aid for patients with metastatic melanoma: results of the randomized controlled trial "PEF-Immun" - Grabbe, Pia; Borchers, Milena; Gschwendtner, Kathrin M.; Strobel, Sophia; Wild, Beate; Kirchner, Marietta; Kälber, Katharina; Rendon, Adriana; Steininger, Julian; Meier, Friedegund; Hassel, Jessica C.; Bieber, Christiane (Deutsches Ärzteblatt, 2024)
Background: Treatment decisions in metastatic melanoma (MM) are highly dependent on patient preferences and require the patients’ involvement. The complexity of treatment options with their individual advantages and disadvantages is often overwhelming. We therefore developed an online patient decision aid (PtDA) to facilitate shared decision making (SDM).